Diatom Physiology Controls Silicic Acid Leakage in Response to Iron Fertilization. Issue 12 (10th December 2019) - Holzer, Mark; Pasquier, Benoit; DeVries, Timothy; Brzezinski, Mark
Abstract : We explore how the iron dependence of the Si:P uptake ratio R Si:P of diatoms controls the response of the global silicon cycle and phytoplankton community structure to Southern Ocean iron fertilization. We use a data‐constrained model of the coupled Si‐P‐Fe cycles that features a mechanistic representation of nutrient colimitations for three phytoplankton classes and that is embedded in a data‐assimilated global ocean circulation model. We consider three parameterizations of the iron dependence of R Si:P, all of which are consistent with the available field data and allow equally good fits to the observed nutrient climatology but result in very different responses to iron fertilization: Depending on how sharply R Si:P decreases with increasing iron concentration, iron fertilization can either cause enhanced silicic acid leakage from the Southern Ocean or strengthened Southern Ocean silicon trapping. Enhanced silicic acid leakage occurs if decreases in R Si:P win over increases in diatom growth, while the converse causes strengthened Southern Ocean silicon trapping. Silicic acid leakage drives a floristic shift in favor of diatoms in the subtropical gyres and stimulates increased low‐latitude opal export. The diatom contribution to global phosphorus export increases, but the lower diatom silicon requirement under iron‐replete conditions reduces the global opal export. Regardless of R Si:P parameterization, the global response of the biological phosphorus and silicon pumps is dominated by the Southern Ocean. The Si isotope signature of opal flux becomes systematically lighter with increasing iron‐induced silicic acid leakage, consistent with sediment records from iron‐rich glacial periods. Key Points: Iron fertilization leads to silicic acid leakage if the Si:P uptake ratio decreases sharply enough to overwhelm increased diatom growth Silicic acid leakage increases low‐latitude opal export, while the Southern Ocean dominates increases in diatom organic matter export Silicic acid leakage in response to iron fertilization produces isotopically lighter biogenic opal flux